2003
DOI: 10.3168/jds.s0022-0302(03)74015-6
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Effects of a Monensin Premix on Milk Fatty Acid Content During Subacute Ruminal Acidosis in Dairy Cows

Abstract: The effects of a monensin premix on milk fatty acid content during grain-induced subacute ruminal acidosis (SARA) in Holstein cows receiving a total mixed ration was investigated. Six multiparous, rumen-fistulated Holstein cows were used in a two-treatment, two-period crossover design with 6-wk periods. Experimental treatments were either a monensin premix or a placebo premix. At the beginning of wk 4, SARA was induced in experimental cows for a 10-d period using a grain challenge model. The administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…Monensin supplementation had little effect on milk FA composition and the only effects were increased ( P =0·03) concentrations of cis 9-16:1 and cis 9,12-18:2 in milk fat. Proportion of CLA in milk fat was similar for cows supplemented or not with monensin, which would agree with the results of Mutsvangwa et al (2003). There have been some suggestions that monensin can modify milk FA composition by inhibiting biohydrogenation of 18:2 and increasing the content of 18:1 (Fellner et al 1997; Sauer et al 1998).…”
Section: Resultssupporting
confidence: 92%
“…Monensin supplementation had little effect on milk FA composition and the only effects were increased ( P =0·03) concentrations of cis 9-16:1 and cis 9,12-18:2 in milk fat. Proportion of CLA in milk fat was similar for cows supplemented or not with monensin, which would agree with the results of Mutsvangwa et al (2003). There have been some suggestions that monensin can modify milk FA composition by inhibiting biohydrogenation of 18:2 and increasing the content of 18:1 (Fellner et al 1997; Sauer et al 1998).…”
Section: Resultssupporting
confidence: 92%
“…The proportion of 16:1 tended (P = 0.08) to increase (+6%) in milk fat of cows fed MO compared with those fed no MO. The concentration of CLA in milk fat was similar for cows supplemented or not with MO, which would agree with the results of Mutsvangwa et al (2003). There have been some suggestions that MO can modify milk FA profile by inhibiting biohydrogenation of linoleic acid (18:2) and increasing the content of monounsaturated 18:1 FA (Fellner et al, 1997;Sauer et al, 1998).…”
Section: Essential Oils From Plant Extracts Have Been Reportedsupporting
confidence: 85%
“…Therefore, it is of great significance to study the damage of SARA in ruminants, and finding an effective strategy to prevent the occurrence of SARA is critical to ruminant farming industry. Previous studies have demonstrated that probiotics (Enemark, 2008), buffering agent (Erdman, 1988), and monensin (Mutsvangwa et al, 2003) can be used in alleviating SARA. However, the heavy use of buffering agent may be justified during an acute problem with SARA.…”
Section: Introductionmentioning
confidence: 99%